TIME AND COST MANAGEMENT ANALYSIS OF THE FORMWORK AND REINFORCEMENT WORK (COLUMNS, BEAMS, AND SLABS) FOR THE 2ND FLOOR AMENITIES IN THE OFFICE BUILDING DEVELOPMENT PROJECT OF THE KNOWLEDGE HUB BSD CITY - Nosi, Leonardus; Bangun, Sempurna; Sembiring, Kristina; Naibaho, Pio Ranap Tua (University Muhammadiyah Jakarta, 2024)
A project is a business activity that is complex, non-routine in nature, has limited time, budget and resources and has its own specifications for the product to be produced. With the existence of several limitations in working on a project, an organization in the project is needed to manage the resources (equipment, budget, and workforce) owned so that they can carry out synchronous activities so that the project objectives can be achieved. In construction projects every building material uses concrete material, which in practice, especially in the last 10-20 years, concrete has been increasingly used. To obtain the planned concrete shape and to harden it, we need formwork or moulds. The Knowledge Hub BSD City office building project is built on an area of 1.1 hectares covering a building area of 54,956 m2 consisting of 11 floors. This location is located on Jalan Raya BSD Barat, Sampora, Cisauk District, Tangerang Regency, Banten Province. The research objective for the analysis of these calculations starts from calculating the duration of each job based on cost and time calculations obtained from existing technical drawing data. The research method used is the calculation of formwork (columns, beams and slabs) through the Microsoft Excel application.